Fueling culture : 101 words for energy and environment - Szeman, Imre, 1968-; Wenzel, Jennifer, 1969-; Yaeger, Patricia (Fordham University Press, 2017)
A collection of brief reflections on keywords related to energy, including the various substances and forces with which humans have produced energy, and their past, present, and future implications for values, politics, culture, and environment.